Johannes Hoornbeeck, a monumental 17th century Dutch theologian continuities in his thinking on doctrine and life - Hofmeyr, J. W. 1947- (2016)
In this article on the 17th-century Johannes Hoornbeeck, the initial focus is on the Further Reformation of which Hoornbeeck was a representative. The focus then switches to Hoornbeeck himself: the story of his life, of his written legacy and of Hoornbeeck as a 17th-century theologian and representative of the Further Reformation. This first article focuses especially on his contributions in the field of practical theology and homiletics, polemics and pastoral theology. In a later article, the focus will move to his contributions as a systematic theologian, as an historian, as a missiologist, and as a socially engaged theologian with an irenical and ecumenical orientation, in spite of him being a strong polemicist. Though some aspects related to scholasticism are already raised in the current article, a further and deeper analysis of scholastic aspects in his thinking will be highlighted in the second article.
Keywords: Hoornbeeck -- Voetius -- Further Reformation -- Practical theology